Extrinsic Localized Excitons in Patterned 2D Semiconductors. (17th May 2022) - Yagodkin, Denis; Greben, Kyrylo; Eljarrat, Alberto; Kovalchuk, Sviatoslav; Ghorbani‐Asl, Mahdi; Jain, Mitisha; Kretschmer, Silvan; Severin, Nikolai; Rabe, Jürgen P.; Krasheninnikov, Arkady V.; Koch, Christoph T.; Bolotin, Kirill I.
Abstract : A new localized excitonic state is demonstrated in patterned monolayer 2D semiconductors. The signature of an exciton associated with that state is observed in the photoluminescence spectrum after electron beam exposure of several 2D semiconductors. The localized state, which is distinguished by non‐linear power dependence, survives up to room temperature and is patternable down to 20 nm resolution. The response of the new exciton to the changes of electron beam energy, nanomechanical cleaning, and encapsulation via multiple microscopic, spectroscopic, and computational techniques is probed. All these approaches suggest that the state does not originate from irradiation‐induced structural defects or spatially non‐uniform strain, as commonly assumed. Instead, it is shown to be of extrinsic origin, likely a charge transfer exciton associated with the organic substance deposited onto the 2D semiconductor. By demonstrating that structural defects are not required for the formation of localized excitons, this work opens new possibilities for further understanding of localized excitons as well as their use in applications that are sensitive to the presence of defects, e.g. chemical sensing and quantum technologies. Abstract : D. Yagodkin, K. Greben, A. Eljarrat, S. Kovalchuk, M. Ghorbani‐Asl, M. Jain, S. Kretschmer, N. Severin, J. P. Rabe, A. V. Krasheninnikov, C. T. Koch, K. I. Bolotin A new excitonic state is observed in 2D semiconductors after electron beam functionalization. The state is bright, has a very narrow photoluminescence peak at cryogenic temperatures, and survives up to room temperature. It is shown that this state is not related to intrinsic defects in transition metal dichalcogenides but is associated with molecules on the surface of the material.